The Moringa Seed (Moringa oleifera, L.) Extracts Potentially Reduce the Effects of Clothes Washing Wastewater on Growth of Green Beans (Vigna radiata) - Merymistika Y. Afred; Bibiana D. Tawa; Pius D. Ola (Journal of Applied Chemical Science, 2012)
A study concerning the use of Moringa seed (Moringa oleifera, L.) extracts to reduce the influence of clothes washing wastewater on growth of green bean (Vigna Radiata) has been conducted. The study aimed to determine the effective dose of coagulants prepared from moringa seed extracts (400, 600, 800, 1000, and 2000 mg/L) on germination of green beans in wastewater. The results showed that the optimum dose of coagulant was 2000 mg/L. The treatments with various doses of coagulants indicated significantly different except for the dose of 1000 mg/L and 2000 mg/L (P < 0.05). The stem height and leaf watering with coagulant water were 25.9 cm and 14.1 cm2, respectively, while by the tap water were 24.3 cm and 10.99 cm2, respectively. Those results conclusively indicated that the water coagulant prepared from moringa seed extracts promotes growth of the vigna radiata.